PENGARUH PENERAPAN GREEN ACCOUNTING DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN (STUDI KASUS: PERUSAHAAN SEKTOR ENERGY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018 – 2022) - Atep Sudirman; Devi Astriani; Rohma Septiawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Global warming is a hot topic of discussion. The impact of this phenomenon is very significant on the survival of humans and other living creatures. Tight competition in the industrial world encourages companies to improve their performance in order to survive and achieve their goals of obtaining maximum profits. However, sometimes in an effort to achieve these goals, they ignore the environmental impacts resulting from their business activities. Legitimacy theory recommends that companies provide a sense of confidence to the public so that they accept the company's activities and performance. The aim of this research is to determine the effect of implementing Green Accounting and Corporate Social Responsibility (CSR) on Company Value in Energy sector companies listed on the Indonesia Stock Exchange. This research uses secondary data, namely annual reports and financial reports of energy companies listed on the IDX for the 2018 - 2022 period. It uses 12 energy sector companies as samples and uses multiple regression analysis as an analysis technique in this research. Data analysis obtained shows that the Green Accounting and CSR variables have a significant effect on Company Value.